Evaluation The Effect of Magnetized green tea extracts on The Bone Density And Osteoporosis In The Experimental Rats By DXA-Scan - Nour Abd alrazaq Hassan; Tahseen Hussain Mubarak; Nameer Fadhel Gheaeb (Diyala Journal of Medicine, 2019)
Background: The study showed that magnetized green tea has effects on bone regeneration, bone density and the amount of this effect depends on the intensity of the power and the frequency of the electromagnetic field emitted. The properties of green tea change when exposed to magnetic fields so that its contents change from metals and organic materials and be flexible and easy to penetrate the cell wall and increase the speed of proliferation. This change in properties is necessary for organ growth and the amount of effect depends on the strength of the electromagnetic field and the time of exposure. The study showed that is an improved in quality of the green tea when exposed to the electromagnetic field with significant changes in the minerals and organic matter .Therefore it’s penetration into cell wall would be facilitated, which can accelerate ordinary diffusion of green tea. That is vital for growth and development of different organs .Exposing the green tea to strong magnetic fields affect in the green tea mineral content , and its effects depend on the "strength of the magnetic field and exposure time".